Perceived impact of physiotherapy-related debates on the social platform “X” on physiotherapists’ professional development and knowledge acquisition: a cross-sectional study - Maryam Alasfour; Zainab Lajami; Abdullah Algashami (BMC Medical Education)
Abstract Background In Saudi Arabia, the social media platform “X” (formerly known as “Twitter”) is widely utilized by healthcare professionals. This study aimed to assess the perceived impact of physiotherapy-related debates on X on the professional development and knowledge acquisition of physiotherapists. Methods A cross-sectional, online survey-based study was conducted among licensed physiotherapists in Saudi Arabia. The study followed established international reporting guidelines, including the Strengthening the Reporting of Observational Studies in Epidemiology, Checklist for Reporting Results of Internet E-Surveys, and Checklist for Reporting Results of Internet E-Surveys. Results A total of 188 physiotherapists participated, with the majority (n = 143;76.1%) actively using X. Many participants indicated positive impacts on their perspectives or approaches to physiotherapy, enhancement of their critical thinking skills, and acquisition of new knowledge or insights (n = 73; 51.0% agreed, n = 26; 18.2% strongly agreed). Furthermore, participants reported gaining knowledge of research findings (n = 45; 31.5% agreed, n = 44; 30.8% strongly agreed) and new treatment techniques (n = 48; 33.6% agreed, n = 42; 29.4% strongly agreed). Additionally, 30.1% (n = 43) agreed and 6.3% (n = 9) strongly agreed that these debates influenced their professional development, whereas 46.2% (n = 66) remained neutral. Conclusions Physiotherapy-related debates on the social media platform X positively impacted physiotherapists’ perspectives by enhancing critical thinking and knowledge acquisition. Such online debates may serve as valuable tools for professional development in physiotherapy practice.